MARI BERWIRAUSAHA AGAR INDONESIA MENJADI NEGARA MAJU DAN KAYA - Sugiantono A.R. (STIE Mandala Jember, 2012)
Indonesia will be the developed country that respected by other countries if the number of citizens who work as small entrepreneurs, medium entrepreneurs, especially large entrepreneurs are many, because Indonesia should have a number of medium and large entrepreneurs at least 2% of total population, and has at least 20% of total population are small entrepreneurs. With many entrepreneurs will be more state revenue gained from taxes, the more tax revenues will increase national income. Great national income, so income of the people will be higher as well. Higher incomes would indicate people prosperity/welfare getting better, better people welfare shows Indonesia is a developed country.